MEDIA PEMBELAJARAN YANG DIGUNAKAN GURU BIMBINGAN DAN KONSELING DALAM PELAKSANAAN LAYANAN PEMINATAN (Penelitian Pada Guru Bimbingan dan Konseling di SMA Negeri dalam Wilayah Kota Banda Aceh) - Putra Setiawan; Nurhasanah Nurhasanah; Said Nurdin (JIMBK: Jurnal Ilmiah Mahasiswa Bimbingan & Konseling, 2018)
Media is one of the most important components in the learning process. Without the use of media, teaching and learning activities will be difficult to do optimally. This study aims to find out the instructional media used guidance and counseling teachers in the implementation of specialization services. This research includes descriptive research type using qualitative approach. The subject of this research is the guidance and counseling Teachers from SMA Negeri 2 Banda Aceh, SMA Negeri 3 Banda Aceh, and SMA Negeri 5 Banda Aceh. Data collection techniques used were interviews and documentation. While the data analysis technique is done with three steps, namely data reduction, data display and verification.The results showed that the learning media used by guidance and counseling teachers in the implementation of specialization services, namely (1) Audio media, namely radio tape and cassette recording; (2) Projection visual media that includes projectors and slides; (3) Non-projected visual media in the form of whiteboards and wall magazines; (4) Print media, ie brochures, modules, magazines, and reference books; (5) Graphics media in the form of diagrams and career trees; and (6) Audio-visual media that includes movies/videos and laptops. The conclusion of this research is guidance and counseling teacher using audio media, visual projection media, non-projection visual media, print media, and audio visual media in specialization service process.